Transformational Leadership Management of Madrasah Principals Based on Inspirational Motivation and Individual Consideration at Mts Pakis Cilongok - Shoffa Saifillah Al Faruq; Lourena Fitri May; Anis Wati Mamluah; Kholil Lur Rochman; Nur Alfiana; Azhar Jaafar (Attractive : Innovative Education Journal, 2026)
Transformational leadership in education is considered an effective strategy to enhance school quality, build a positive organizational culture, and foster student character. Mts Pakis in Gununglurah Village, Cilongok, Banyumas, stands out as an alternative agroforestry-based school for children from underprivileged families and serves as a unique example of transformational leadership in practice. This study aims to analyze the transformational leadership practices of the madrasah principal in strengthening organizational culture and improving educational quality. The research employs a qualitative approach with a literature study method. Data were collected through a review of primary literature discussing Mts Pakis and transformational leadership concepts, as well as interviews with Kang Is, the principal of Mts Pakis. Data analysis was conducted using Avolio and Bass's transformational leadership framework. The results indicate that the principal implements two main dimensions of transformational leadership: inspirational motivation through a vision integrated with local values and the Pakis principles (Piety, Achievement, Knowledge, Integrity, Sincerity), and individualized consideration by giving attention to both students and volunteers despite limited resources. Therefore, this study confirms that transformational leadership is not only effective in formal schools with adequate support but can also succeed in community-based alternative madrasahs. These findings are expected to enrich educational leadership studies with perspectives of local wisdom and environmental sustainability.